Pengaruh Shopee Paylater dan Promosi Flash Sale terhadap Impulse Buying melalui Kepercayaan sebagai Variabel Intervening: (Studi Kasus pada Pengguna Marketplace Shopee di Mojokerto) - Sindy Khoirunnisa; Eny Setyariningsih; Budi Utami (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
Rapid technological developments in the industrial revolution 4.0 era have brought major changes in various areas of life, including internet technology which has had an impact on the business world. One online business that is growing rapidly is the Shopee marketplace. Using features on the Shopee marketplace without being wise causes uncontrolled impulse buying behavior. This research aims to determine the effect of Shopee paylater and flash sale promotions on impulse buying through trust as an intervening variable (case study of Shopee marketplace users in Mojokerto). This research uses a quantitative approach with the population of Shopee marketplace users in Mojokerto. The sample consisted of 300 respondents, with a questionnaire as a data collection tool. The data analysis method uses path analysis with smartPLS 4 software. The research results show that shopee paylater has a positive and significant effect on trust in the shopee marketplace, flash sale promotions have a positive and significant effect on trust in the shopee marketplace, trust has a positive and significant effect on impulse buying in the shopee marketplace , shopee paylater has a positive and significant effect on impulse buying on the shopee marketplace, flash sale promotions have a positive and significant effect on impulse buying on the shopee marketplace, shopee paylater has a positive and significant effect on impulse buying through trust in the shopee marketplace, flash sale promotions have a positive and significant effect against impulse buying through trust in the Shopee marketplace.